Hic manus ob patriam pugnando vulnera passi, czyli o kontynuacji programu ideowego Sali Rycerskiej Zamku Królewskiego w litografii Franciszka Kosteckiego: Hic manus, ob patriam pugnando vulnera passi, or the continuation of the ideological programme of the Knight’s Hall from the Royal Castle in Warsaw in lithographies by Franciszek Kostecki - Jakubowski, Tomasz (Artifex Novus, 2020)
The article refers to the ways in which the iconographic programme of the Knight’s Hall from the Royal Castle in Warsaw was portrayed in 19th-century graphics. The ideas devised by King Stanisław August in the spirit of the Enlightenment were extended by Franciszek Kostecki in lithography from 1819-1831. It depicts the apotheosis of Jan Henryk Dąbrowski, Tadeusz Kościuszko and Prince Józef Poniatowski, and was complemented with a quotation from Virgil’s Aeneid. The subsequent graphics were mainly executed in the workshops of Louis Letronne (c. 1821) and Józef Swoboda (published in Lviv in 1863). The last echo of extending the ideas of heroic leaders and the pantheon of national heroes is the painting by Jerzy Kossak ‘On the threshold of eternity’ from 1935 which depicts Józef Piłsudski entering Wawel Cathedral, and Józef Poniatowski and Tadeusz Kościuszko welcoming him there on the stairs.